Desempenho das exportações de café solúvel do Brasil - Carvalho, Jullyanna Nair de (2014)
The relative participation of Brazil in the international market for soluble coffee has reduced despite Brazil being the world's largest exporter in this market. It is worth noting that the international market is the most relevant for Brazilian soluble coffee, since, even with the increase in domestic consumption in recent years, about 75% of the soluble produced in the country is exported. Thus, the objective of this study was to analyze the performance of Brazilian exports of soluble coffee. The methodologies used were the Revealed Comparative Advantage (RCA) and Constant market share (CMS) models. The RCA was analyzed in the period from 1986 to 2010. In order to analyze the CMS we considered three periods: 1991-1996 to 1997-2000, 1997-2000 to 2001-2005 and 2001-2005 to 2006-2010. Brazil has revealed comparative advantage throughout the analyzed period, although this advantage has been reduced. Regarding the effects that most contributed to the performance of Brazilian soluble coffee exports, the competitiveness effect was responsible in reducing Brazilian soluble coffee exports in the first two periods, while in the third period, in which there was an effective growth of Brazilian soluble coffee exports, the world trade growth effect was the most important.